Tourism and Memories of Home Migrants, Displaced People, Exiles and Diasporic Communities - Marschall, Sabine (Tourism and Cultural Change, 2017)
This book investigates ‘home’ and ‘homeland’ as destinations of touristic journeys and adds to recent scholarly interest in the intersection between tourism and migration. It covers the temporary visits and journeys in search of home and homelands by migrants, displaced people, exiles and diasporic communities in a wide range of different geographical and historical contexts. Personal and collective forms of memory are shown to play a key role in the motivation for, and experience of, such journeys. The volume contributes to the investigation of the tourism–memory nexus as it conceptualizes memory as underpinning touristic mobility, experience and performativity.  Based on ethnographic case studies and other types of qualitative empirical research, the chapters of this book foreground individual touristic experiences, emotions, memories, perceptions, the search for identity and a sense of belonging. The book will be of interest to students and researchers in the fields of tourism, heritage, anthropology, identity studies, memory studies and migration/diaspora studies